Islamic Religious Education in the Digital Era: A Critical Analysis of Social Media Framing of Millennial Preaching - Nining Sariningsih; Khozin Khozin (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
The digital era has significantly transformed the face of Islamic da’wah, particularly in its interaction with Millennials and Gen Z in Indonesia. Social media has become a new arena for spreading religious messages, packaged in a visual, concise, and emotional manner. This study aims to analyze how the framing of Islamic da’wah on social media is constructed and perceived by the younger generation, as well as its impact on the substance of Islamic religious education. The method used is library research with a qualitative-descriptive approach, analyzed critically through framing theory (Entman, Pan & Kosicki), the theory of the mediatization of religion, and socio-religious studies in digital society. The findings indicate that social media framing tends to encourage a populist and lightweight style of da’wah, which shifts the focus of religious education from deep value cultivation to instant spiritual consumption. Meanwhile, Millennials and Gen Z respond positively to this approach as it is considered more communicative and relevant to their digital lifestyle, although it carries the risk of reducing the depth of religious understanding. This study recommends the need for a more critical, reflective, and balanced approach to da’wah—between form and substance—so that Islamic religious education continues to play its role in shaping holistic religious character amid the currents of digital globalization.